Molecular characterization of CBF transcription factor genes in oat - Bräutigam, Marcus; Gustavsson, Åsa; Zakhrabekova, Shakhira; Olsson, Björn; Olsson, Olof (MTT, 2004)
By EST sequencing we identified 2866 different genes from a cold induced cDNA library from the British winter oat variety Gerald (see other abstract by Bräutigam et al). Among these there are several genes similar to cold and/or drought-induced genes previously identified in rice, wheat, rye, barley and Arabidopsis. More than 100 genes encoded putative transcription factors. Of particular importance for the regulation of cold acclimation is the CBF transcription factor family genes, which have important regulatory roles in the cold signalling pathway. In all CBF proteins analysed so far, a characteristic AP2-binding domain has been found. This interacts with a DRE/CRT regulatory element and activates transcription of downstream cold and dehydration responsive genes. Four CBF factor sequences were found in the oat EST collection, belonging to at least 2 different gene families. A full-length cDNA clone from one such gene, denoted AsCBF1, was isolated and sequenced. This revealed a 909 bp long open reading frame (ORF) encoding a putative protein of 303 aa that contain an AP2-binding domain. By semiquantitative RT-PCR analysis we showed that expression of the AsCBF1 gene was induced already 30 minutes after cold induction at +4oC. By chromosomal walking an additional 457 bp upstream of the AsCBF1 translational start codon was isolated. A TATAA-box was then found as well as several other potential regulatory elements including a Myc-recognition site. These elements will now be further characterised both in vitro and in vivo. CBF genes will also be used as genetic engineering tools to develop more cold tolerant oat.
Keywords: Ka; transcription factor; cold induction; CBF